The Prospect Of Modernising Rural Areas Using Information And Communication Technology: A Case Study In Kota Marudu, Sabah. - Romzi A.; Anna Lynn A. B.; Ros Aiza M. M. (Universiti Malaysia Sabah, 2024)
The purpose of this study was to investigate the potentials in achieving the goals of modernizing rural areas in Kota Marudu, Sabah using Information and Communication Technology (ICT). The data were collected through a self administered questionnaire and was later analyzed used Statistical Package for Social Sciences (SPSS). 300 rural people who were staying in Kota Marudu, Sabah with a mean age of 27 were chosen as respondents. Besides that, this study found that ICT was considered to have a significant relationship to the prospect of modernizing the rural areas. The study had specifically revealed that ICT had its significant impacts towards the prospect of modernizing rural areas in the economic, social and political aspects. This study had also found that the influence of ICT towards the present rural areas administrative aspect shows its significant relevance. Moreover, based on the findings, the researchers had preliminary discussed how ICT should be widespread in Kota Marudu, Sabah which could be effectively be dealt with the current higher poverty profile in this selected area.